Zastosowanie mnożników fundamentalnych w wycenie aktywów kapitałowych : empiryczny test w warunkach polskiego rynku kapitałowego (1998-2004) - Sklinda, Sławomir (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this paper is empirical verification of fundamental multiples as a capital asset pricing tool. Three multiples were examined: earnings to price, operating cash flow to price and book value to equity. Further, capitalization as a size proxy was added to the explanatory variables. Applied methodology was based on Fama and French [Fama, French 1992], however necessary adjustment had to be done. The survey was conducted on monthly data over the period 1998-2004. Achieved results do not favor fundamental multiples in expected returns estimation and well documented on Western equity markets relations between firms' returns and its multiples do not hold on Polish Stock Exchange. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 227-235